OPTIMALISASI PERAN INTERMEDIASI BANK SYARIAH TERHADAP MASYARAKAT MISKIN (Studi pada Bank Sulselbar Kab.Bone) - Marni M (Institut Agama Islam Negeri (IAIN) Bone, 2022)
This study discusses the Optimization of the Intermediation Role of Islamic Banks Against the Poor (Study at Bank Sulselbar Kab.Bone). The data analysis that was used in this study is a description of the analysis. This research was made because there is still a lack of people involved in financing for the poor at Bank Sulselbar. The research conducted is descriptive qualitative research using field research methods, namely observations and interviews conducted by analyzing data sourced from the research location or place, namely Bank Sulselbar in implementing the intermediation role of Islamic banks for the poor. This research is also a library research.Based on the result of the research that gained is the role of intermediation of Islamic Bank toward the poor in increasing the the life of poor society in Bank SulSelbar is not already exist. This is caused the most of poor society are not able yet to involved into bank system. However, Islamic bank of Islamic sulSelBar keep helping the following poor society to pulfill their needs or to increase their business owned those society, namely those found in the Hasanah Titik Foundation by channeling tabarru funds such as Zakat, Infaq and Shodaqoh and providing a number of microfinance loans to middle and upper class people who have businesses with the aim of increasing the community's business and will also provide job opportunities for the poor the